Conflict in Caledonia : Aboriginal land rights and the rule of law - DeVries, Laura, 1982- (Law and society series (Vancouver, B.C.), 2011)
"In February 2006, First Nations protesters blocked workers from entering a housing development in southern Ontario. The protest highlighted the issue of land rights and sparked a series of ongoing events known as the "Caledonia Crisis." This powerful account of the dispute links the actions of police, officials, and locals to non-Aboriginal discourses about law, landscape, and identity. DeVries encourages non-Aboriginal Canadians to reconsider their assumptions, to view "facts" such as the rule of law as culturally specific notions that prevent truly equitable dialogue. She seeks out possible solutions in alternative conceptualizations of sovereignty over land and law embedded in the Constitution."--Pub. desc.